CAESAREAN OPERATION FOR VARIOUS TYPES OF DYSTOCIA IN RUMINANTS UNDER FIELD CONDITIONS - Dilipkumar, D; Dhage , G P (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Forty three ruminants belonging to different species were subjected to caesarean operations. In the present study maximum casualties (20 out of 21 animals ) were observed which were handled prior to caesarean. Twenty two out of 43 animals (51.1%) survived after caesarean operation. A very high success rate was observed in animals which were not handled earlier. Twenty two out of 23 animals survived (99%) which were not manipulated before caesarean operation. The results of present study suggested that unwarranted handling of dystocia which are not amicable for normal parturitions should be avoided and subjected to early caesarean operation to achieve high success rate.